Analisis Kesalahan Siswa dalam Menyelesaikan Soal-Soal Pemecahan Masalah Matematika pada Siswa Kelas XI MIA SMA - Azis Azis; Artati Iriana; La Sudin (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The purpose of this study is to find out the errors made by students in solving mathematical problem solving problems in linear programming material. The method in this research is descriptive analysis. This research was carried out at SMA Negeri 2 Lasalimu Selatan, Lasalimu Selatan District, Buton Regency with the population of this research being all students of class XI MIA SMA Negeri 2 Lasalimu Selatan, totaling 40 students using a descriptive method whose main concern was the results of students' mathematics tests on linear programming material. Based on the results of the answers of class XI MIA students at SMA Negeri 2 Lasalimu Selatan which have been analyzed by researchers, it can be seen that the errors made by 20 respondents in 5 question numbers are 8 conceptual errors with a percentage of about 8%, principle errors as many as 35 with a percentage of approx. 35%, and operating errors of 35 with a percentage of about 35%. Respondents made a conceptual error because they did not understand the meaning of the problem in translating into mathematical sentences. Respondents made a principle error because they did not understand the rules or formulas to be used. Respondents made operational errors because they made mistakes in algebraic or arithmetical work. Therefore, it is necessary to pay attention to subject teachers so that students' understanding of understanding concepts, principles, and operations, especially linear programming material, needs to be improved by re-explaining problems that are not understood by these students.